PENGARUH KARAKTERISTIK PERUSAHAAN DAN KEPEMILIKAN INSTITUSIONAL TERHADAP TAX AVOIDANCE (Studi Empiris pada Perusahaan Sektor Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2010-2014) - Fakhria Ahmad Tawang; Ria Nelly Sari; Alfiati Silfi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to examine the effect of firm characteristics (profitability, firm size, capital intensity, inventory intensity, growth) and institusional ownership on tax avoidance. The population of this study was manufacturing companies listed on Indonesian Stock Exchange in 2010 until 2014. The sample was chosen by purposive sampling method and obtained 41 companies. Data was analyzed by using panel data regression analysis with EViews program 9 version. The results showed that the probability, firm size, and capital intensity has negative effect on tax avoidnace, while growth and institusional ownership has positive effect on tax avoidance. Unfortunately, this study failed to prove that the inventory intensity affects tax avoidance. The results of coefficient of determination (adjusted R2 ) showed that variables of profitability, firm size, capital intensity, inventory intensity, growth, and institusional ownership on tax avoidance amounted to 70,70% while the remaining 29,30% was affected by other variables.Keywords: Firm Characteristics, Institusional Ownership, Tax Avoidance